A disaggregated approach to analyzing the effect of electricity on carbon emissions: Evidence from African countries - Kizito Uyi Ehigiamusoe (Energy Reports, 2020)
This paper investigates the effects of electricity consumption and generation on carbon emissions in 25 African countries for the 1980-2016 period. Specifically, it examines the effects of diverse electricity sources (e.g. hydro, oil, natural gas, coal) and renewable electricity output on carbon emissions. It employs estimation techniques that are appropriate for cointegrated panels such as Dynamic Ordinary Least Squares (DOLS), Fully Modified Ordinary Least Squares (FMOLS) and Augmented Mean Group (AMG). The panel cointegration tests reveal a cointegration relationship between the variables. The estimation results show that electricity consumption has a detrimental effect on carbon emissions, while renewable electricity output mitigates carbon emissions in African countries. Moreover, electricity generation from oil, natural gas and coal have detrimental effects on carbon emissions while electricity generation from hydro alleviates carbon emissions. This implies that electricity consumption and generation are significant determinants of carbon emissions in African countries, hence efforts to abate carbon emissions should incorporate them in order to achieve sustainable development.
Keywords: 330; Sustainable development; African countries; Carbon emissions; Electricity consumption; Electricity generation; Renewable electricity output